Techniques for creating quality questions - Atikah, Nur Shadrina; Arbeni, Wawan; Saiban, Nabila; Harahap, Sindy Claudia; Damara, Viola Disti (Lembaga Riset Mutiara Akbar, 2026)
This study aims to examine the technique of creating high-quality questions as an important component in learning evaluation. Well-structured and systematic questions play a role in objectively measuring student competency achievement and reflecting the true level of understanding. The research method used in this study is a literature study by reviewing various relevant sources, such as books, scientific journals, and educational policy documents. The study was conducted by analyzing the concepts, principles, and procedures for creating questions that are in accordance with learning objectives and student characteristics. The results of the study indicate that creating high-quality questions must consider several key aspects, including the suitability of indicators to learning objectives, language clarity, student cognitive levels, and the principles of validity, reliability, objectivity, and practicality. In addition, the selection of question types, such as written tests, performance tests, and non-test instruments, needs to be tailored to the competencies to be measured. By applying appropriate question-building techniques, the learning evaluation process can be more effective and accurate. High-quality questions not only help teachers assess student learning outcomes but also serve as a basis for making improvements and developing the learning process towards a better direction.